Pengaruh Motivasi Belajar Terhadap Hasil Belajar Siswa pada Mata Pelajaran Instalasi Penerangan Listrik - Bobby Wansep Putra; Oriza Candra (Jurnal Pendidikan Teknik Elektro, 2023)
This research aims to find out how significant the effect of a Learning Motivation on Student Learning Outcomes in the Class XI TITL Electrical Lighting Installation subject at SMK N 1 Padang. This study uses a type of quantitative approach research and is correlational. The subjects in this study were all students of class XI TITL in the 2022/2023 academic year. There were two classes, one class was used for research class and the other class was for research instrument testing. Data collection used a questionnaire and documentation, the questionnaire used a Likert scale score of four which had been expertly validated by an expert lecturer at the Department of Electrical Instruments, after which a trial was carried out and it was distributed to respondents. Data analysis techniques in this study used prerequisite analysis techniques, simple linear regression tests and t-tests to determine the significant effect of the independent variables on the independent variables, as well as the determinant coefficient test to determine the significant magnitude of the independent variables on the dependent variable. The results of this study indicate that there is a significant influence of learning motivation on student learning outcomes in the class XI Electrical Lighting Installation subject at SMK N 1 Padang.